Russia SimSmoke: the long-term effects of tobacco control policies on smoking prevalence and smoking-attributable deaths in Russia. Issue 6 (12th July 2013) - Maslennikova, Galina Ya; Oganov, Rafael G; Boytsov, Sergey A; Ross, Hana; Huang, An-Tsun; Near, Aimee; Kotov, Alexey; Berezhnova, Irina; Levy, David T
Abstract : Background: Russia has high smoking rates and weak tobacco control policies. A simulation model is used to examine the effect of tobacco control policies on past and future smoking prevalence and premature mortality in Russia. Methods: The Russia model was developed using the SimSmoke tobacco control model previously developed for the USA and other nations. The model inputs population size, birth, death and smoking rates specific to Russia. It assesses, individually and in combination, the effect of seven types of policies consistent with the WHO Framework Convention on Tobacco Control (FCTC): taxes, smoke-free air, mass media campaign, advertising bans, warning labels, cessation treatment and youth access policies. Outcomes are smoking prevalence and the number of smoking-attributable deaths by age and gender from 2009 to 2055. Results: Increasing cigarette taxes to 70% of retail price, stronger smoke-free air laws, a high-intensity media campaign and comprehensive treatment policies are each potent policies to reduce smoking prevalence and smoking-attributable premature deaths in Russia. With the stronger set of policies, the model estimates that, relative to the status quo trend, smoking prevalence can be reduced by as much as 30% by 2020, with a 50% reduction projected by 2055. This translates into 2 684 994 male and 1 011 985 female premature deaths averted from 2015–2055. Conclusions: SimSmoke results highlight the relative contribution of policies to reducing the tobacco health burden in Russia. Significant inroads to reducing smoking prevalence and premature mortality can be achieved through strengthening tobacco control policies in line with FCTC recommendations.